Self-correction of wrongful convictions: is there a "System-level" confirmation bias in the Swedish legal system's appeal procedure for criminal cases?—Part II. (14th August 2018) - Lidén, Moa; Gräns, Minna; Juslin, Peter
Abstract: In this study, we propose that confirmation bias may not only be present in the behaviours of individual agents in the judicial system but can also be recognized at a 'system-level' as an inability to self-correct, that is, an inability to acquit wrongfully convicted who appeal or petition for a new trial. To assess the self-correctional ability, a very low error rate of wrongful convictions in the District Courts in 2010–2014 was tentatively assumed. An empirical review of appeals (Part I) and petitions for new trials (Part II) in the Courts of Appeal and Supreme Court between 2010 and 2014 was carried out to evaluate to what extent these legal remedies can be expected to change wrongful convictions into acquittals. Realistic assumptions and empirical estimates of real-world statistics suggest that at least 34.67% of the wrongfully convicted remained convicted despite the possibility both to appeal and petition for a new trial. A robustness analysis was performed to ascertain that the conclusions hold under a wide variety of assumptions about the unknown statistics. According to additional analyses the odds of an acquittal were low even for appeals referring to new innocence supportive evidence and for private individuals claiming to be innocent of, e.g. assault or murder the odds of being granted new criminal trials were particularly low.